Justice and Equal Opportunities in Health Care - Harris, John (Bioethics, 1999)
The principle that each individual is entitled to an equal opportunity to benefit from any public health care system, and that this entitlement is proportionate neither to the size of their chance of benefitting, nor to the quality of the benefit, nor to the length of lifetime remaining in which that benefit may be enjoyed, runs counter to most current thinking about the allocation of resources for health care. It is my contention that any system of prioritisation of the resources available for healthcare or of rationing such resources must be governed by this principle. This can have apparently paradoxical conclusions in that it can seem wasteful to give someone with a very slim chance of a lifesaving treatment the same priority as someone with a much better chance. In an important and thoughtful recent paper, Julian Savulescu has concentrated on this apparent weakness and has argued for a particular conception of the good or benefit to be achieved by a healthcare system which purports to demonstrate the inadequacies of an equal opportunities approach to prioritisation and to replace it with an altogether better account. This paper will show that a rational ‘reasons based consequentialism’ is more in line with the equal opportunities approach, which I defended some time ago in these pages, than with that of Savulescu. I shall then examine more closely the conception of equal opportunities in health care and show that if we give weight to an individual's reasons, and what is expected to be good for them, we will opt for exactly the equality based account of distributive justice that I have recommended.